Computers - Wood, John, 1990-; Kissock, Heather (Awesome infographics., 2021)
Presents the history of the computer, and explores how it has evolved over time. Defines digital language, hardware, software, the internet, and supercomputers. Includes color illustrations, a timeline, a quiz, a glossary, and additional resources.